A study on the effectiveness of the concerned parents' satisfaction of the UPV Balay Balay Center in providing quality childcare to children ages 3-5 years old of the UPV Personnel. - Blanco, Nilo
Recent governmental programs reflect the states recognition of the high human. Based on the findings of the study, the researchers recommend the following; 1) The center must continue to adhere to its objective in providing quality childcare to 3-5 years old children of UPV personnel. Apart and financial costs of children, women and families in crisis. Such programs are meant to support and protect Filipino homes against the threatening effect of the rising socialproblems and economic demands. The increasing number of two-income households where both parents are obliged to work to cope with their financial needs has a direct effect on: 1) working women who have to face tremendous responsibilities both as a mother-wife and an employee; 2) growing children who in their most critical years are the most vulnerablehuman aspect requiring so much time, attention, guidance and affection; 3) the family being the fundamental group of society and the natural environment for the growth and well-being of all its members and particularly children, should be afforded the necessary protection and assistance so that it can fully assumed its responsibilities within the community (UN conventions on the Rights of the Child). In answer to this need for support system for women, especially working women, and their children, as expressed in thePhilippine Plan for Gender-Responsive Development (PPGD, 1995-2005) that the University of the Philippines in the Visayas established its childminding center, the UPV Balay-Balay Center in 1999. It has been in operation for three years serving 37 children, thirteen of which are children of UPV Personnel. Three of the center's primary objectives are : 1) to respond to one concern of a sector of UPV personnel enabling working parents, especially the mothers to fully concentrate on their jobs, thereby generating better work performance ;2) to attend to the welfare and care of children especially of UPV personnel by providing an opportunity for socialization, appropriate nurturing and values orientation at early levels of development and; 3) to provide a secure, homely and stimulating environment appropriate to the development of the 3-5 years old children of UPV personnel. It is in this light that the researchers took interest in evaluating the effectiveness of and the UPV personnel-parents' satisfaction with the UPV Balay-balay Center i providing quality childcare to their children ages 3-5 years old.To answer the objectives of the study, the descriptive-survey research design was used. The respondents were the eleven out of thirteen UPV personnel who have been availing of the services of the center since the start of its operations in 1999. Taking into considerations the different categories of variables: sex, age highest educational attaintment, average yeraly income, period of availment of the center services and he frequency of availment of the center services, results of the study showed that parents perceived the UPV Balay-balay Center to be effective un delivering its services. Ironically however, the parents are less satisfied with the center in providing quality childcare since it falls short of the standards required in establishing a childminding center based on the following categories : site, provision of facilities and program materials and schedule of activities. Based on the findings f the study, the researchers recommend the following: 1) The center must continue to adhere to its objective in providing quality childcare to 3-5 years old children of UPV personnel. Apart from this, the center would defeat its purpose; 2)The center's site, facilitites, program meterials and schedule of activities must be upgraded. However, this would largely depend on the availability of funds. The UPV administration's support for the most part is very important on this aspect; 3) Parents should be properly oriented of their roles as partners of the center that they may actively participate and get involved with its different activities. This will enable them to monitor the development of their children as well as fulfill their responsibilities as parents; 4)As support system, the management should provide lectures on Parents Effectiveness and Early Childhood Care and Development meetings and programs to update them on the recent trends of parenting and child-rearing practices; 5)Regular monitoring and evaluation of the center should be conducted to ensure that the young children are continuously provided with the environment to grow and achieve their fullest potentials. It is likewise important to know where areas of improvement may lie.Effective monitoring and evaluation depends, to a considerable extent, on the quantity and quality of data and information generated, it is important that adequate and relevant records are kept.